"Done more for me in a fortnight than anybody done in all me life." How welfare rights advice can help people with cancer - Moffatt Suzanne; Noble Emma; Exley Catherine (BMC, 2010)
Abstract Background In the UK many people with cancer and their carers do not have easy access to the welfare benefits to which they are entitled adding further strain to the process of dealing with cancer. It is estimated that nine out of ten cancer patients' households experience loss of income as a direct result of cancer, which, due to its socio-economic patterning disproportionately affects those most likely to be financially disadvantaged. In the UK proactive welfare rights advice services accessed via health care settings significantly increase benefit entitlement among people with health problems and this paper reports on a qualitative study examining the impact of a welfare rights advice service specifically designed for people affected by cancer and their carers in County Durham, North East England (UK). Methods Twenty two men and women with cancer or caring for someone with cancer who were recipients of welfare rights advice aged between 35 and 83 were recruited from a variety of health care and community settings. Semi-structured interviews were undertaken and analysed using the Framework method. Results Most of the participants experienced financial strain following their cancer diagnosis. Participants accessed the welfare rights service in a variety of ways, but mainly through referral by other professionals. The additional income generated by successful benefit claims was used in a number of ways and included offsetting additional costs associated with cancer and lessening the impact of loss of earnings. Overall, receiving welfare rights advice eased feelings of stress over financial issues at a time when participants were concerned about dealing with the impact of cancer. Lack of knowledge about benefit entitlements was the main barrier to accessing benefits, and this outweighed attitudinal factors such as stigma and concerns about benefit fraud. Conclusions Financial strain resulting from a cancer diagnosis is compounded in the UK by lack of easy access to information about benefit entitlements and assistance to claim. Proactive welfare rights advice services, working closely with health and social care professionals can assist with the practical demands that arise from dealing with the illness and should be considered an important part of a holistic approach to cancer treatment.